DETERMINANTS OF THE CHOICE OF MARKETING CHANNEL AMONG COCOYAM FARMERS IN SOUTH EAST NIGERIA - Opata; Patience. Ifeyinwa (Journal of Animal and Plant Sciences, 2018)
Choice of market channels has been studied from different angles in the developing countries. However, model identifying the relative significance of household socio-economic and institutional attributes influencing channel choices of cocoyam at household level in South East Nigeria have never been estimated. In this study, discrete choice of multinomial logit model was used to estimate the market channel choices. Multistage sampling technique was used and data was collected from 300 small holder cocoyam farmers. Data for the study was collected from sampled market outlets in South east Nigeria between September 2015 and October 2016. Multinomial logit regression model (MNL) was used to analyze factors influencing the choice of marketing channels. The results of this study showed that age, storage costs, volume of cocoyam marketed, distance to the market, purpose of farming and farm size were found to significantly influence choice of household cocoyam market outlet. Households that incurred higher transaction costs in form of storage, transportation, handling more volume of cocoyam were more likely to sell through market channel 3 as oppose to local market where he or she sell to consumer in channel 1 as well as market channel 2 where he sells through semi-urban market. Therefore, the need for credit that will enable them to pay all the transaction costs needed to make high gross margin. Choice of channel 3 ensure high gross margins consequently credit to offset all the transaction costs will be the key in accessing the best marketing channel. Key wards: Marketing channel; Multinomial logit; Cocoyam farmers; South east Nigeria as Agricultural Transformation Agenda (ATA), Root and
Keywords: NA